Islamic Local Culture Commodification in Disruption Era Tourism Industrial - Azizah, Intan Nur (LPPM UIN Saizu Purwokerto, 2024)
This study aims to find out how to synergize the demands of globalization - especially the commodification of the tourism industry's culture - with the development of the distinctiveness of the kejawen group as part of a tourist attraction? What strategy needs to be developed so that the kejawen group as a cultural identity or local wisdom subject of its supporting community is still protected, but it is also hoped that it can accommodate the demands of economic globalization which has commodified culture? The subject in this study was the Aboge Islamic group in Purbalingga and Banyumas Regencies. This study uses ethnographic methods. Ethnographic research methods are used to find theories based on the field data obtained. The era of the global economy demands that all elements of culture can be made into commodities, eventually, the term cultural commodification was born. In other words, the commodification of culture is the process of producing cultural objects as commodities that are traded through the cultural industry by following market rules. The results of this study indicate that the Islamic Aboge group in Purbalingga and Banyumas areas has carried out cultural commodification as a strategy to maintain its existence in society. Several traditions that developed later result in new traditions to maintain the existence of the Aboge group as a cultural identity. Cultural commodification is also able to accommodate the demands of economic globalization as an entertainment art in the form of tourist attractions.